Negotiation of Gender Relations Meaning among Female Interpretation Community in Housing and Village Settlement - Lestari, Sri Budi; Wiryopranoto, Suhartono; Simatupang, GR Lono Lastoro (Universitas Negeri Semarang, 2014)
The sitcom of Husbands fearing Wives (SSTI-Suami-Suami Takut Istri), is one of the private television sitcoms which highlights violence as a joke to provoke laughter of its audiences. In SSTI, the joke involves the concept of gender, exchanging the role of women and men which has been socially and culturally constructed. One of the main objectives of this study is to analyze the role of the interpretation community in understanding the gender relations in SSTI sitcom. The study aims to discover the media interpretation by a group of female audiences living in the village and sub-district of Tembalang, Semarang. The results show that the negotiation of interpretation community on SSTI sitcom is not in line with the goal of the media; because the nature of men and women roles that are exchanged is interpreted as an â€œabnormalâ€ relation. Therefore, the hierarchical power relation between men and women which tends to disadvantage women, for interpretation community is regarded as a normal & natural.Tayangan sinetron komedi Suami-suami Takut Istri (SSTI), merupakan salah satu program televisi swasta yang menonjolkan kekerasan sebagai lelucon untuk tujuan memancing tawa. Dalam prakteknya SSTI melibatkan konsep jender, yang mempertukarkan sifat-sifat perempuan dan laki-lakiÂ sebagai hasil kontruksi secara sosial maupun kultural. Salah satu tujuan penelitian ini ingin menganalisis peran komunitas interpretasi dalam pemaknaan tentang relasi jender pada tayangan sinetron SSTI. Penelitian ini berlangsung pada penonton perempuan yang tinggal di perumahan dan perkampungan wilayah kecamatan Tembalang, kota Semarang. Hasil penelitian menunjukkan bahwa negosiasi komunitas interpretasi pada tayangan sinetron SSTI tidak sejalan dengan arahan media karena ternyata sifat laki-laki dan perempuan yang dipertuarkan dimaknai sebagai relasi yang tidak â€˜normalâ€™. Dengan demikian relasi kuasa hirarkis antara laki-laki dan perempuanÂ yang cenderung merugikan perempuan bagi komunitas interpretasi justru dianggap sebagai suatu relasi yang normal serta dipahamiÂ sebagai kodrat kultural.